Design and Simulation of Magnetorheological Brake Supporting Downhill Van Truck - Hoang, Quang-Tuan; Bui, Huu-Dieu; Tran, Thanh-Tung (JST: Engineering And Technology For Sustainable Development, 2023)
Depressing the brake when the vehicle is moving downhill for a long time will have a bad effect on the car's brake system. Typically, the phenomenon of friction, wear, and temperature rise occurs at the brake pads. These can be the causes of brake failure. This paper presents the idea of designing and simulating magneto-rheological brake (MRB) model to assist van trucks downhill without interfering with the traditional braking system. Research on brake models using: Magneto-rheological fluid (MRF), a smart material that is gradually being applied in many fields of science and technology. The operation of this type of brake is based on the inherent advantages of MR fluids such as continuously changing dynamic range and fast response, actively changing the viscosity of the fluid when changing the magnetic field applied to the coil. In order to improve safety and initiative in the braking process of the car. The study presents the process of calculating and simulating the braking torque generated from this brake model. Thereby helping to open a new direction for the traditional brake system in cars as well as contributing to the development of the automobile industry in general.